Clinical picture and treatment of 2212 patients with common variable immunodeficiency - Gathmann, Benjamin; Mahlaoui, Nizar; Gérard, Laurence; Oksenhendler, Eric; Warnatz, Klaus; Schulze, Ilka; Kindle, Gerhard; Kuijpers, Taco W; van Beem, Rachel T; Guzman, David; Workman, Sarita; Soler-Palacín, Pere; et al. (Journal of allergy and clinical immunology, 2014)
BACKGROUND: Common variable immunodeficiency (CVID) is an antibody deficiency with an equal sex distribution and a high variability in clinical presentation. The main features include respiratory tract infections and their associated complications, enteropathy, autoimmunity, and lymphoproliferative disorders. OBJECTIVE: This study analyzes the clinical presentation, association between clinical features, and differences and effects of immunoglobulin treatment in Europe. METHODS: Data on 2212 patients with CVID from 28 medical centers contributing to the European Society for Immunodeficiencies Database were analyzed retrospectively. RESULTS: Early disease onset (<10 years) was very frequent in our cohort (33.7%), especially in male subjects (39.8%). Male subjects with early-onset CVID were more prone to pneumonia and less prone to other complications suggesting a distinct disease entity. The diagnostic delay of CVID ranges between 4 and 5 years in many countries and is particularly high in subjects with early-onset CVID. Enteropathy, autoimmunity, granulomas, and splenomegaly formed a set of interrelated features, whereas bronchiectasis was not associated with any other clinical feature. Patient survival in this cohort was associated with age at onset and age at diagnosis only. There were different treatment strategies in Europe, with considerable differences in immunoglobulin dosing, ranging from 130 up to 750 mg/kg/mo. Patients with very low trough levels of less than 4 g/L had poor clinical outcomes, whereas higher trough levels were associated with a reduced frequency of serious bacterial infections. CONCLUSION: Patients with CVID are being managed differently throughout Europe, affecting various outcome measures. Clinically, CVID is a truly variable antibody deficiency syndrome.
Keywords: dospělí; Bronchiectasis; intravenózní imunoglobuliny; Female; Pneumonia; Europe; věk při počátku nemoci; Autoimmunity; dítě; předškolní dítě; pneumonie; Adult; ženské pohlaví; opožděná diagnóza; Adolescent; Lymphoproliferative Disorders; běžná variabilní imunodeficience; lidé; Survival Analysis; Immunoglobulins, Intravenous; Evropa; splenomegalie; Splenomegaly; Common Variable Immunodeficiency; retrospektivní studie; bronchiektazie; Male; Delayed Diagnosis; Child, Preschool; lymfoproliferativní nemoci; analýza přežití; autoimunita; Child; Age of Onset; mužské pohlaví; Retrospective Studies; mladiství; Humans